If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(W + 3) + -3(2W + -1) = W Reorder the terms: 4(3 + W) + -3(2W + -1) = W (3 * 4 + W * 4) + -3(2W + -1) = W (12 + 4W) + -3(2W + -1) = W Reorder the terms: 12 + 4W + -3(-1 + 2W) = W 12 + 4W + (-1 * -3 + 2W * -3) = W 12 + 4W + (3 + -6W) = W Reorder the terms: 12 + 3 + 4W + -6W = W Combine like terms: 12 + 3 = 15 15 + 4W + -6W = W Combine like terms: 4W + -6W = -2W 15 + -2W = W Solving 15 + -2W = W Solving for variable 'W'. Move all terms containing W to the left, all other terms to the right. Add '-1W' to each side of the equation. 15 + -2W + -1W = W + -1W Combine like terms: -2W + -1W = -3W 15 + -3W = W + -1W Combine like terms: W + -1W = 0 15 + -3W = 0 Add '-15' to each side of the equation. 15 + -15 + -3W = 0 + -15 Combine like terms: 15 + -15 = 0 0 + -3W = 0 + -15 -3W = 0 + -15 Combine like terms: 0 + -15 = -15 -3W = -15 Divide each side by '-3'. W = 5 Simplifying W = 5
| tan(4x+5)=-6 | | 15x=24+7x | | -.8x+.25=.2+.33x | | 6m+4.25=55.25 | | 3x+4(x-3)=36 | | 6+4.25=55.25 | | 2a^2*2a^2= | | a^2*a^2= | | 11u-8u=12 | | 8(6y-3)-(8y+4)= | | 2x+4(x-3)=36 | | x2/3-5=31 | | 6b^4-18b^3-60b^2=0 | | y=0.22x | | 0.09x+4.92=12.75 | | 2x*4x=28 | | -11.7=35.1 | | 5=v+4 | | 3(3-2y)+y=y-5(y+2) | | -12x-14=7(x-4) | | 17-3(y-1)=0 | | 2(x-2)+3(x-1)=0 | | 2b=6+b | | 3-3b-b=2b-5-4 | | 0=x^2-24 | | 2x-18=3x-5 | | 3x+b+12-5x=22 | | t=4t^2-10t+8 | | 0.166(x-42)=0.833 | | (4x^2-4x+109)=0 | | 2x+5(7-2x)=2(1-3x) | | 3/5v=3/7 |